The behaviour and effects of beam-end buckling in fire using a component-based method. (15th May 2017) - Quan, Guan; Huang, Shan-Shan; Burgess, Ian
Highlights: A component-based model to simulate the local buckling of Class 1 to 2 steel beams in fire. Model can deal with post-buckling deformation reversal. Incorporate the model into the software Vulcan. Model validated against ABAQUS modelling. Influence of the steel beam buckling on the adjacent connections investigated. Abstract: A combination of beam-web shear buckling and flange buckling at the ends of steel beams is very commonly observed during full-scale fire tests. This can affect the behaviour of the steel beams, as well as on their adjacent connections, under fire conditions. This phenomenon has not previously been sufficiently investigated and cannot be simulated in high-temperature global frame analysis, which could potentially lead to unrealistic results being used in structural fire engineering design. In this research, a component-based beam-end buckling element has for the first time been created for Class 1 and 2 beams. The beam-end buckling element is composed of nonlinear springs, respectively representing the buckling of beam flange and web, also considering the interaction between these two buckling phenomena. Each spring is able to deal with loading-unloading-reloading force-deformation paths. A significant challenge is to enable the flange buckling spring to deal with post-buckling deformation reversal. The buckling element has been implemented into the structural fire engineering frame analysis software Vulcan, to be used adjacent to existing connection elements in frame modelling. The buckling element has been verified against ABAQUS finite element modelling on isolated beams. It is shown that the newly created component-based buckling element is able to simulate the effects of beam-end shear buckling in the web and local buckling of the bottom-flange, with satisfactory accuracy. The influence of the buckling element on the bolt-row force distribution within the adjacent connection element has been investigated. Analyses using isolated beams indicate that the implementation of the buckling element considerably improves the prediction of connection force resultants. A general observation from numerical studies with and without the buckling element is that beam-end buckling seems to reduce the connection component forces generated at elevated temperatures.